The Polish Contribution to Enhance the Culture of Medical Security - Małgorzata WIŚNIEWSKA (Communications of International Proceedings, 2022)
We are the first Polish scientists to be commissioned by the International Atomic Energy Agency Department of Nuclear Security to conduct a nuclear security culture self-assessment study in hospital. We conducted the Coordinated Research Project (CRP) in collaboration with the International Atomic Energy Agency and two private Polish subsidiaries that use radioactive sources and materials. In this article, we publish a sample report of a survey conducted between 2015 and 2018 in one of the three Affidea Poznań departments: the Department of Radiotherapy Poznań. We describe the course of the survey, including its plan and method of implementation. Then we present selected methods used in the project to analyze, summarize and present the results obtained. This CRP proved to be a great challenge for our team. We brought a lot of experience from this study and working with two very specific types of organizations. Studying and researching security culture, especially when you are just breaking new ground, is a great chellenge.
Keywords: culture; human; management; medical; security; self-assessment